2019
DOI: 10.1186/s12974-019-1597-y
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic endothelin-1 overexpression promotes neural progenitor cells proliferation and differentiation into astrocytes via the Jak2/Stat3 pathway after stroke

Abstract: BackgroundEndothelin-1 (ET-1) is synthesized and upregulated in astrocytes under stroke. We previously demonstrated that transgenic mice over-expressing astrocytic ET-1 (GET-1) displayed more severe neurological deficits characterized by a larger infarct after transient middle cerebral artery occlusion (tMCAO). ET-1 is a known vasoconstrictor, mitogenic, and a survival factor. However, it is unclear whether the observed severe brain damage in GET-1 mice post stroke is due to ET-1 dysregulation of neurogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 70 publications
1
32
1
Order By: Relevance
“…In addition, our study showed that the phosphorylation levels of JAK2/STAT3 are downregulated after IR injury, while pretreatment with mild hypothermia and leptin can upregulate these and thus attenuate IR injury; these results confirmed that activating JAK2/-STAT3 pathway can attenuate IR injury. However, our results are in dispute with some studies, which showed that the phosphorylation levels of JAK2/STAT3 are increased after IR injury [51][52][53]. We think it has something to do with the time of the models.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, our study showed that the phosphorylation levels of JAK2/STAT3 are downregulated after IR injury, while pretreatment with mild hypothermia and leptin can upregulate these and thus attenuate IR injury; these results confirmed that activating JAK2/-STAT3 pathway can attenuate IR injury. However, our results are in dispute with some studies, which showed that the phosphorylation levels of JAK2/STAT3 are increased after IR injury [51][52][53]. We think it has something to do with the time of the models.…”
Section: Discussioncontrasting
confidence: 99%
“…Increased neuronal connectivity is considered to be one of the conditions that promote functional recovery following SCI ( 48 ). These results suggested that the STAT3-RNAi-transfected NSCs produced highly developed neurons that served a potentially useful role in neurogenesis, consistent with the results of previous studies ( 14 , 23 ). Wu et al ( 49 ) used microRNA-15a to downregulate STAT3 in mice following SCI, following which a superior functional recovery was observed.…”
Section: Discussionsupporting
confidence: 92%
“…Immunofluorescence staining analysis showed that the targeted inhibition of STAT3 induced the differentiation of NSCs into neurons, as the neuronal marker β3-tubulin ( 24 ) was found to be expressed more frequently in the LV-STAT3 group compared with that in the CL and LV-CL groups. However, GFAP, a specific marker of astrocytes ( 23 ), was expressed at significantly lower levels in the LV-STAT3 group compared with those in the other two groups ( Fig. 1E-G ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Astrocytes are the main type of glial cells, accounting for more than 50% of the total volume of brain cells. ET-1 produced by activated astrocytes binds to its cognate receptor expressed on astrocytes and causes neuroinflammation [ 14 ], potentiated by increased expression of matrix metalloproteinase-9 (MMP-9) and vascular endothelial growth factor-A (VEGF-A) in astrocytes, ultimately resulting in brain edema [ 15 ]. In this study, we investigated whether UTI alleviates the severity of TBI by suppressing the astrocyte activity and limiting the production of ET-1 and inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%